Fanst det eit eige namn Solli i Noreg i millomalderen? - Myrvoll, Klaus Johan (NAMN OG NEMNE, 2019)
This article discusses the alleged existence of a medieval Norwegian personal name Solli, which E. H. Lind lists in hisÂ monumental Norsk-isländska dopnamn ock ï¬ngerade namn från medeltiden (1905-15, 1931) and derives etymologically from the verb svella ’to swell’. It is argued that this was no independent name formation in medieval times, but rather a spelling variant or a hypocorism of the common Old Norse name SÇ«lvi(r), whereas the Modern Norwegian name Solle (Sølle) is, more likely, a continuation of the more marginal Old Norse name SÇ«rli. The argu-ments for making such a division between old and new Solle are primarily the great variance in spellings of the name SÇ«lvi(r) in the medieval sources as well as the overlapping geographical dis-tribution of these name forms. Some of the persons whose names are spelled â€¹Solleâ€º etc. in the sources are tentatively linked to persons who clearly had the name SÇ«lvi(r). A sound change from SÇ«lvi(r) to Solli is problematic, though, and the new form is explained as either a pure spelling variant where the v is left out (as in other spellings of the same name), or a hypocorism where the consonant cluster has been simpliï¬ed (as in Modern Swedish nick-name equivalents such as Hjalle for Hjalmar and Kalle for Karl).